Sustainability of a physical activity and nutrition program for seniors - Pasalich, Maria; Lee, Andy; Jancey, Jonine; Burke, Linda; Howat, Peter (Serdi-Editions, 2013)
OBJECTIVE This prospective cohort study aimed to determine the impact of a low cost, home-based physical activity and nutrition program for older adults at 6 months follow-up. DESIGN A follow-up survey was conducted 6 months after program completion via computer-assisted telephone interviewing. The International Physical Activity Questionnaire and the Fat and Fibre Barometer were used to measure physical activity levels and dietary behaviours, respectively. Self-reported height, weight, waist and hip circumferences were obtained. Changes over three time points of data collection (baseline, post-program, follow-up) and differences between the intervention and control groups were assessed. The use of program materials was also evaluated. SETTING Community and home-based. PARTICIPANTS Insufficiently active 60 to 70 year olds (n = 176, intervention and n = 198, control) residing in suburbs within the Perth metropolitan area.RESULTS A sustained improvement was observed for the intervention group in terms of fat avoidance behaviours (p interaction =.007). Significant improvements were found for strength exercises, fibre intake, body mass index and waist-to-hip ratio at either post-program or follow-up, however the overall effect was not significant. At post-program, the intervention group increased time spent participating in moderate activity by 50 minutes (p >.05), which was followed by a significant decline at follow-up (p <.05). Among intervention group participants, males and females differed with respect to strength exercises and moderate physical activity. CONCLUSION This low-cost physical activity and nutrition intervention resulted in a sustained improvement in fat avoidance behaviours and overall short-term gains in physical activity. Future studies for older adults are recommended to investigate gender-specific behavioural barriers as well as booster interventions which focus on physical activity.